Analisis Dampak Laju Pertumbuhan Penduduk Terhadap Aspek Kependudukan Berwawasan Gender Pada Urban Area Di Kota Serang - Enis Khaerunnisa; Ranthy Pancasasti; Eloh Bahiroh; Ana Susimulyani (Sains: Jurnal Manajemen dan Bisnis, 2017)
In the short term the purpose of this study is to: (1) analyze the trend of population growth rate in Serang City, (2) to analyze the impact of population growth rate on gender aspect of population in urban area in Serang City, (3) to analyze the increasing of environmental pollution and deforestation of the environment, such as flooding in Serang City, (4) identifying strategic steps that need to be done to prevent and control population growth rate toward aspect of population with gender insight on urban area in Serang City. Data obtained in this study were analyzed using 4 methods, namely tabulation analysis, descriptive, Focus Group Discussion (FGD) and Root Case Analysis (RCA). The result of this research are: (1) population growth rate in Serang City shows decreasing trend. In the period 2010-2020, the population growth rate of Serang City dropped from 2.20 percent to 1.52 percent, (2) the increasing number of residents in Serang City currently demands the management of population and good resources in order to avoid problems in the future. The efforts in the management of the population, among others, controlling the population, improving the quality and quality of the population, and utilizing appropriate human and natural resources will make the large population in Serang City become a strong development capital, (3) ideal capacity of an area, namely Serang City to be able to accommodate the maximum rainfall, the current city of Serang gets overloaded capacity of rainfall greater than ideal capacity. Or in other words, high rainfall makes Serang City unable to withstand the volume of rainfall, which is an average of 5.87 m3 / ha, and (4) there are several strategic steps that need to be done to prevent and control population growth rate (2) Improving education and skills, (3) Conserving the environment, (4) Keeping public facilities, and (5) ordering the aspects of population-oriented gender in urban areas in Serang City.